2020
DOI: 10.1021/acs.chemrev.0c00523
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Catalysis Mediated by Synthetic Peptides, Version 2.0: Expansion of Scope and Mechanisms

Abstract: Low molecular weight synthetic peptides have been demonstrated to be effective catalysts for an increasingly wide array of asymmetric transformations. In many cases, these peptide-based catalysts have enabled novel multifunctional substrate activation modes and unprecedented selectivity manifolds. These features, along with their ease of preparation, modular and tunable structures, and often biomimetic attributes make peptides well-suited as chiral catalysts, and of broad interest. Many examples of peptide-cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
109
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(111 citation statements)
references
References 654 publications
(1,466 reference statements)
2
109
0
Order By: Relevance
“…The concept of steric hindrance has been widely used in selective chemical reactions, especially asymmetric synthesis, and tremendous molecular design samples and theoretical rules have been developed in this eld. [152][153][154] Therefore, we believe that there is still enough potential for making good use of steric hindrance with a rational molecular design strategy to further improve the efficiency and stability of perovskite devices. Especially, the combination of previous knowledge on asymmetric syntheses based on steric hindrance and the latest advances in in situ material characterization and theoretical investigations would help us to further explore the mechanism of steric hindrance.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of steric hindrance has been widely used in selective chemical reactions, especially asymmetric synthesis, and tremendous molecular design samples and theoretical rules have been developed in this eld. [152][153][154] Therefore, we believe that there is still enough potential for making good use of steric hindrance with a rational molecular design strategy to further improve the efficiency and stability of perovskite devices. Especially, the combination of previous knowledge on asymmetric syntheses based on steric hindrance and the latest advances in in situ material characterization and theoretical investigations would help us to further explore the mechanism of steric hindrance.…”
Section: Discussionmentioning
confidence: 99%
“…Amino acids and peptides derived thereof are privileged and versatile compounds of paramount importance in organic chemistry, chemical biology, and drug discovery. They are prevalent motifs in a high number of drug candidates [1] and have shown to be powerful catalysts to perform a wide range of chemical reactions in an enantioselective fashion, [2] and effective ligands in the realm of metal‐catalyzed C−H functionalization [3] . Furthermore, it has been demonstrated that increasing the steric bulk of the side‐chains of amino acids within a peptide sequence often results in higher metabolic resistance of the corresponding biomolecule to enzyme degradation as well as in improved biological activity and pharmacokinetics [4] .…”
Section: Introductionmentioning
confidence: 99%
“…Peptide and peptidomimetic catalysts are important for understanding principles of enzymatic catalysis, and they are also useful catalysts in their own right in a variety of synthetic applications, including in the synthesis of natural products. [1][2][3][4] Peptide catalysts provide a middle ground between small molecule organocatalysts and full-length enzymes, retaining the synthetic accessibility of the former, and some aspects of the complex multifunctional, three-dimensional, and chiral environment of the latter. While the rate enhancement and stereoselectivity of most current peptide catalysts is not on the scale of enzymatic catalysis, studying catalytic peptides can increase their synthetic utility.…”
Section: Introductionmentioning
confidence: 99%
“…While the rate enhancement and stereoselectivity of most current peptide catalysts is not on the scale of enzymatic catalysis, studying catalytic peptides can increase their synthetic utility. 3,4 Elements of secondary structure have oen been used in the design of peptide catalysts, [5][6][7][8][9][10] which can serve to orient reactive residues near each other in space to mimic the catalytic triads and dyads of enzyme active sites. The study of ester hydrolysis catalysts has been used as a starting point for more challenging hydrolysis reactions, 11 and has important practical applications itself, 12 such as in the depolymerization of polyester plastics.…”
Section: Introductionmentioning
confidence: 99%